2017
DOI: 10.3233/rnn-170748
|View full text |Cite
|
Sign up to set email alerts
|

Making if-then plans counteracts learned non-use in stroke patients: A proof-of-principle study

Abstract: This observation opens a potential new route to improving stroke rehabilitation. If-then plans may qualify as a viable strategy to overcome the learned non-use of the affected arm. Further research is now required to develop and test therapeutic measures based on this proof-of-principle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…17,18 Although the term "learned nonuse" itself has not appeared in the MS literature, this condition likely commonly follows chronic motor disability in this disease. In contrast, the term is widely used in both the stroke clinical [31][32][33] as well as the experimental neuroscientific literature. [34][35][36] Multiple reports describe persons with MS who have chronically self-restricted limb use and concurrent behavioral compensation, who nonetheless can move substantially more when urged, [37][38][39][40] thus suggesting learned nonuse.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Although the term "learned nonuse" itself has not appeared in the MS literature, this condition likely commonly follows chronic motor disability in this disease. In contrast, the term is widely used in both the stroke clinical [31][32][33] as well as the experimental neuroscientific literature. [34][35][36] Multiple reports describe persons with MS who have chronically self-restricted limb use and concurrent behavioral compensation, who nonetheless can move substantially more when urged, [37][38][39][40] thus suggesting learned nonuse.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Cohen, Bayer, Jaudas, and Gollwitzer (2008, Study 2; see also Miles & Proctor, 2008) observed the suppression of habitual responses using a Simon task paradigm; the Simon task allows to compare the control of habitual responses (e.g., grabbing things presented on the right side of the person with the right arm) as compared to nonhabitual responses (e.g., grabbing things presented on the right side with the left arm). Expanding this research to a clinical sample, Marquardt, Cohen, Gollwitzer, Gilbert, and Dettmers (2017) had stroke patients with a mild to moderate hand paresis perform the Simon task before and after they had formed respective if-then plans. A significant Simon effect (i.e., comparatively faster responding in corresponding trials where things need to be responded to with the arm of the side where the stimulus is presented as compared to noncorresponding trials) was observed in both the affected and the nonaffected arm; however, there was no longer a significant Simon effect for trials that were prepared by forming if-then plans.…”
Section: Goal Intentions Versus Implementation Intentionsmentioning
confidence: 99%
“…In order to adapt to the motor disability that these symptoms generate, patients develop compensatory behaviors characterized by a decrease in the use of their affected arm and an increased use of the opposite arm, despite, in many cases, the functional recovery of their affected arm [ 10 , 17 , 18 ]. This behavior of the non-use of the affected arm, even in the presence of functional capacity, corresponds to the “learned non-use” phenomenon, described as the learned non-use between the impairment and the functional capacity or actual use of the upper limb [ 10 , 19 ].…”
Section: Introductionmentioning
confidence: 99%